2018
DOI: 10.1159/000493369
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Guideline Adherence for T1 Bladder Cancer Treatment and Surveillance: A Retrospective German Multicenter Observation

Abstract: Introduction: To mirror guideline-adherence for pT1 bladder cancer treatment in Northern Germany. Materials and Methods: Overall, 111 patients with pT1 diagnosis were treated at 4 institutions. Guideline-adherence was defined as repeat resection, instillation, and quarterly cystoscopy. Patient characteristics and pathological parameters were assessed. We summarized patients using descriptive analyses and evaluated guideline-adherence within selected subgroups. We created a multivariable model to identify predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Median follow-up for OS ranged from 23 to 130 months across the 21 studies that reported this. 23,27,28,32,33,37,47,49,51,58,66,69,70,74,83,[86][87][88][97][98][99] Likewise, there was no evident trend in survival outcomes with increasing duration of follow-up. Notably, one study by Gordon et al reported the lowest percentage of patients who were alive at follow-up (9.8%) out of the 21 studies, which was seen in patients with HR-NMIBC who did not undergo re-TURBT after a median follow-up period of 50 months.…”
Section: Clinical Outcomes At Follow-upmentioning
confidence: 94%
See 4 more Smart Citations
“…Median follow-up for OS ranged from 23 to 130 months across the 21 studies that reported this. 23,27,28,32,33,37,47,49,51,58,66,69,70,74,83,[86][87][88][97][98][99] Likewise, there was no evident trend in survival outcomes with increasing duration of follow-up. Notably, one study by Gordon et al reported the lowest percentage of patients who were alive at follow-up (9.8%) out of the 21 studies, which was seen in patients with HR-NMIBC who did not undergo re-TURBT after a median follow-up period of 50 months.…”
Section: Clinical Outcomes At Follow-upmentioning
confidence: 94%
“…16,17,27,31,33,34,36,37,42,45,46,[50][51][52]54,59,63,65,68,69,72,74,75,77 Twelve studies reported the use of mitomycin C in high-risk patients. 23,28,30,46,48,64,66,70,72,[79][80][81] Treatment rates ranged from 2% to 53% in 9 studies, with few studies reporting its use in all patients (rate of 100% in 3 studies). In 7 of the 11 studies (64%), mitomycin C 23,28,46,48,64,66,72 Adjuvant and intravesical chemotherapy in HR-NMIBC (not including mitomycin C) were rarely used and reported in a small number of studies (4 55,58,66,67 and 8, 23,28,32,33,51,70,…”
Section: Treatment Patternsmentioning
confidence: 99%
See 3 more Smart Citations